Clinical reasoning as midwifery: A Socratic model for shared decision making in person-centred care - Gunby, Julie D.; Lockhart, Jennifer Ryan (2022)
Shared decision making has become the standard of care, yet there remains no consensus about how it should be conducted. Most accounts are concerned with threats to patient autonomy, and they address the dangers of a power imbalance by foregrounding the patient as a person whose complex preferences it is the practitioner's task to support. Other corrective models fear that this level of mutuality risks abdicating the practitioner's responsibilities as an expert, and they address that concern by recovering a nuanced but genuinely directive clinical role. Cribb and Entwistle helpfully categorize models of shared decision making as ‘narrower’ and ‘broader’ and praise the latter's ‘open-ended and fully dialogical ways of relating’. However, they stop short of providing a philosophical account of how that dialogue works. In this paper, a nurse–midwife and a philosopher collaborate to argue that the Socratic model of dialogue offers a solution to the practitioner–patient dilemma. In the Theaetetus, Socrates compares dialogical reasoning to ‘midwifery with all its standard features’. By means of a three-way analogy, elements of midwifery practice are used to illuminate features of Socrates' claim that his dialogue is like midwifery; those features are then translated into an approach to shared decision making as the ‘midwifery of good thinking’ which both midwives and physicians would do well to adopt. A key concept that emerges is the need for practitioners to make a risk-confidence assessment of the particular content of any decision to appropriately modulate their role in the practice of shared decision making.
Keywords: Socrates; Shared decision making; Risk assessment; Plato; person-centred care; Midwifery; Dialogue